Rethinking Sanctioning for Offenders with Mental Health Issues: A Balanced Justice Approach - Sloas, Lincoln B. (American journal of criminal justice, 2023)
The public’s perspective regarding sanctioning offenders, especially violent and nonviolent, tend to support either a rehabilitative or balanced approach to justice. This study aims to better understand perspectives on sanctioning violent and nonviolent mental health offenders. We draw on a survey of 575 college students from a large university in the south. We assess public perceptions of whether successful reform is possible for violent and nonviolent mental health offenders, if they are willing to work to reform, and if they deserve treatment. The results highlighted a more rehabilitative attitude towards nonviolent mental health offenders and a balanced approaach to violent mental health offenders. These results suggest the importance of considering alternative approaches to sanctioning mental health offenders, including the use of crisis intervention teams and mental health courts rather than a strict adherence to punitive measures.